Comparative evaluation of oral health status of chronic kidney disease (CKD) patients in various stages and healthy controls. (15th July 2013) - Tadakamadla, Jyothi; Kumar, Santhosh; Mamatha, G. P.
ABSTRACT Objective To compare caries, oral hygiene and periodontal status of chronic kidney disease (CKD) patients in different stages and healthy controls. Design Seventy‐four patients diagnosed with CKD and 150 healthy age and sex matched controls were recruited from General Hospital of Udaipur, India. Each subject was examined for caries by decayed, missing and filled teeth (DMFT) index, oral hygiene by simplified oral hygiene index (OHI‐S) while gingival and periodontal status were assessed by Loe and Silness gingival and Community Periodontal Index, respectively. All the examinations were conducted by a single investigator. Results Study subjects presented significantly lower caries experience than the control group but no significant difference was observed among the subjects in various stages of CKD. The mean gingival index score for study group (1.88) was more than twice to that of control subjects (0.92). Stage of kidney disease influenced the gingival and oral hygiene status which decreased as the stage progressed. The overall prevalence of periodontal pockets (70.3%) in diseased subjects was significantly higher than controls (18.9%). More than three quarters (78.9%) of the patients with stage 5 CKD exhibited deep periodontal pockets. Conclusions Oral hygiene, gingival, and periodontal status decreased as the stage of CKD increased and was worse among study subjects that the controls. Dental caries did not differ significantly with the stage of the renal disease but was significantly lower among study subjects than the controls.